Effect of Potassium Iodide and Glutathione on Color Change and Remineralization Potential Induced by Silver Diamine Fluoride Application - Salma Mohammed ElSabaa; Ahmed El Banna; Dina Ahmed El Refai (University Library System, University of Pittsburgh, 2024)
Purpose: To evaluate the effect of applying potassium-iodide (KI) and glutathione (GSH) on silver-diamine fluoride (SDF) induced tooth discoloration as well as their effect on its remineralization potential. Methods: To examine color change, cervical dentinal demineralized cavities were performed mesially and distally in 16 human premolars. Glass-ionomer restoration (GIC) was applied and allocated to four groups I-IV according to the following pre-treatments: No pre-treatment, SDF, SDF+KI, SDF+20%(wt) GSH. Spectrophotometric evaluation of samples at time intervals: 1,7 and 14 days of GIC application. To examine the effect of remineralization, 21 bovine dentin blocks were divided into groups I-III: SDF, SDF + KI, and SDF + GSH. Vickers microhardness was measured, before and after demineralization and after 7 days of treatment. Results: Spectrophotometric results after 14 days for groups I-IV were:1.29±0.18, 12.24±0.19, 2.19±0.32 and 4.76±0.19 respectively. Groups III and IV showed significant reduction in ΔE compared with group II, although they showed significant increase in ΔE compared with group I (p<0.001). KI showed better management of color changes than GSH. The microhardness test results after treatment application to demineralized dentin for Groups I-III were: 30.81±20.87, 30.59±16.42, 24.69±13.21, respectively. All groups showed significantly increased microhardness of demineralized dentin (P ≤ 0.05), which was comparable to that of Group I. Conclusion: Application of KI and GSH after SDF significantly minimized color changes without affecting the remineralizing effect of SDF.